Excellent Treatment Outcomes in Children Treated for Tuberculosis Under Routine Operational Conditions in Cape Town, South Africa. (5th July 2017) - Osman, Muhammad; Lee, Kevin; Du Preez, Karen; Dunbar, Rory; Hesseling, Anneke C; Seddon, James A
Abstract : HIV infection increases the risk of developing tuberculosis (TB), but our understanding of HIV's impact on risk of mortality for children treated for TB is limited. We aimed to identify predictors of mortality in children treated for drug-susceptible TB. Abstract: Background: Tuberculosis (TB) remains a leading cause of death in children globally. It is recognized that human immunodeficiency virus (HIV) infection increases the risk of developing TB, but our understanding of the impact of HIV on risk of mortality for children treated for TB is limited. We aimed to identify predictors of mortality in children treated for drug-susceptible TB. Methods: A retrospective analysis of all children (<15 years of age) routinely treated between 2005 and 2012 for drug-susceptible TB in Cape Town was conducted using the programmatic electronic TB treatment database. Survival analysis using Cox regression was used to estimate hazard ratios for death. Logistic regression was used to estimate the odds of unfavorable outcomes. Results: Of 29519 children treated for and notified with TB over the study period, <1% died during TB treatment and 89.5% were cured or completed treatment. The proportion of children with known HIV status increased from 13% in 2005 to 95% in 2012. Children aged <2 years had an increased hazard of death (adjusted hazard ratio [aHR], 3.13; 95% confidence interval [CI], 1.78–5.52) and greater odds of unfavorable outcome (adjusted odds ratio [aOR], 1.44; 95% CI, 1.24–1.66) compared with children aged 10–14 years. HIV-infected children had increased mortality compared to HIV-negative children (aHR, 6.85; 95% CI, 4.60–10.19) and increased odds of unfavorable outcome (aOR, 2.01; 95% CI, 1.81–2.23). Later year of TB treatment was a protective predictor for both mortality and unfavorable outcome. Conclusions: We demonstrate a dramatic improvement in HIV testing in children with TB over time and excellent overall treatment outcomes. HIV infection and young age were associated with increased risk of death and unfavorable outcome.